The role of extracorporeal life support in the management with severe idiopathic pulmonary artery hypertension undergoing lung transplantation: are those patients referred too late? - Sabashnikov, Anton (J Thorac Dis, 2019)
BACKGROUND: Idiopathic pulmonary artery hypertension (iPAH) is a relatively minor indication for lung transplantation (LTx) with comparatively poorer outcomes. Extracorporeal life support (ECLS) in various forms is increasingly being used in the management of this entity. However, the data and experience with this therapy remains limited. We evaluated the role of ECLS in the management of severe iPAH patients as a bridge to LTx as well as post LTx support. METHODS: A retrospective analysis of iPAH patients that received LTx between January 2007 and May 2014 was performed. Early- and mid-term outcomes were analyzed for this patient cohort. Also, early and mid-term outcomes after LTx were compared to the control group of patients with other diagnoses using unadjusted analysis and 1:3 propensity score matching. RESULTS: Of 321 LTx performed during the study period in our centre 15 patients had iPAH as a cause of end-stage lung disease. Four iPAH (27%) patients were bridged to LTx utilizing ECLS in the form of veno-arterial ECMO and extra-corporeal CO(2) removal device, whereas 9 patients (60%) required ECLS support for primary graft dysfunction (PGD) after surgery. Patients with iPAH required more frequently on-pump LTx, both pre and post LTx ECLS, and had significantly lower pO(2)/FiO(2) ratio at 24, 48 and 72 hours after LTx. Also iPAH patients had significantly longer ICU and hospital stay. Whereas the incidence of postoperative bronchiolitis obliterans syndrome (BOS) and rejection was comparable to the control group, overall cumulative survival with up to 6 years follow-up was significantly poorer in the iPAH group. After propensity score matching, the results in terms of postoperative outcomes remained as in the unadjusted analysis. CONCLUSIONS: ECLS is an essential tool in the armamentarium of any lung transplant program treating iPAH with a potential of bridge patients to transplantation and to overcome graft dysfunction after LTx. Despite utilization of ECLS in the management of iPAH, the outcomes in terms of primary graft failure and survival remain poor compared to patients with other diagnoses.